Prevalence and Stigma of Postpartum Common Mental Disorders in the Gurage Region of Ethiopia: A Mixed-Methods Observational Cohort Study - Monaghan, Sophia; Akale, Meseret Ayalew; Demeke, Bete; Darmstadt, Gary L. (Frontiers in Psychology, 2021)
Objectives Depression is a vastly underdiagnosed illness in low-income countries that disproportionately affects women. We aimed to evaluate the prevalence of common mental disorders in newly postpartum women, and stigma associated with mental health reporting in an Ethiopian community using a validated World Health Oranization survey. Methods The Self Reporting Questionnaire (SRQ) for psychological distress was administered in Amharic by nurses to 118 women aged 18-45 years who had given birth in the prior three months in the Glenn C. Olsen Memorial Primary Hospital in Yetebon. Mental health stigma among the four nursing staff was assessed using Link and Phelan's Components of Stigma. Results Among 118 women surveyed, 18% had a probable common mental disorder using the SRQ 4/5 cutoff and 2% admitted to suicidal thoughts. Presence of stigma in the healthcare staff was verified, including labeling, stereotyping, separating, and status loss and discrimination. Conclusion Postpartum mental health disorders as well as stigma against such diagnoses are common in the Yetebon community. There is an urgent need for increased availability of properly trained and supervised healthcare staff in the identification and referral of postpartum women with common mental disorders.